SUSTAINABLE DEVELOPMENT IN EMERGING ECONOMIES: THE STRATEGIC IMPORTANCE OF GREEN FINANCE - Sharma, Shruti (ShodhKosh: Journal of Visual and Performing Arts, 2024)
It has become clear that green finance allows emerging economies to strengthen environmental sustainability, as these countries face the problem of economic expansion and damage to nature at the same time. This paper studies why green finance is crucial for accomplishing sustainable development goals (SDGs) by managing finances to support low-carbon and climate-friendly growth. Different financial instruments such as green bonds, sustainable investment funds, environmental credit lines, and green government fiscal policies are examined to see how effective they are in spurring efforts toward the environment. By studying empirical studies and secondary records provided by the World Bank, IMF, and regional development banks, the paper looks into the growth, factors holding back, and benefits green finance has in India, Brazil, South Africa, and Indonesia. It looks at the regulations, institutional structure, and ties between the public and private sectors that affect green finance. It is noted by the report that undergoing economies have increased their use of renewables, promoted green farming, and made use of low-emission train systems; however, green financing is not enough to ensure the changes. Difficulties including policy unpredictability, not enough awareness, high fees, and insufficient reliability on investors are still things that hinder growth. The paper urges improving regulations, making things clearer, encouraging investments in green technologies, and developing solid green financial providers to overcome the funding problem. It further points out that countries in the global north should make financial contributions to enable countries in the global south to advance in green technology. Overall, it is emphasized in this study that green finance can bring about better, more stable, and sustainable economies while dealing with mounting climate-related problems. Making Greener financing common in their finance systems gives developing countries a chance to support a sustainable and healthy environment for future generations.